Secondary health conditions in persons with a spinal cord injury for at least 10 years: design of a comprehensive long-term cross-sectional study. (June 2013) - Adriaansen, Jacinthe J. E.; van Asbeck, Floris W. A.; Lindeman, Eline; van der Woude, Lucas H. V.; de Groot, Sonja; Post, Marcel W. M.
<x xml:space="preserve">Abstract</x> Purpose: To describe the prevalence of secondary health conditions (SHCs) (urinary tract and bowel problems, pressure ulcers, spasticity, musculoskeletal and neuropathic pain, sexual dysfunction, respiratory and cardiovascular disorders) in persons with long-term spinal cord injury (SCI), and to explore the impact of SHCs on fitness, active lifestyle, participation and well-being. Methods: A time since injury (TSI)-stratified cross-sectional study among 300 persons between 28- and 65-year-old with a SCI for at least 10 years. Strata of TSI are 10–19, 20–29, and 30 or more years. All eight Dutch rehabilitation centres with a SCI unit will participate. Participants will be invited for a 1-day visit to the rehabilitation centre for an aftercare check-up by the local SCI rehabilitation physician (neurological impairment, SHCs and management), physical tests by a trained research assistant (lung function, wheelchair skills, physical capacity), and they will be asked to complete a self-report questionnaire in advance. Results: Not applicable. Conclusion: This study will provide knowledge on the health status and functioning of persons aging with SCI living in the Netherlands. This knowledge will help us to develop predictive models for the occurrence of SHCs and to formulate guidelines to improve health care for persons with long-term SCI.